HUMAN RESOURCE MANAGEMENT PATTERNS IN INDONESIA’S CONSTRUCTION COMPANIES - Susilowati, Fajar; Prawent, Herlita; Puspitasari, Evi (Journal of Applied Engineering Science, 2021)
Research in several countries from different continents related to human resources in construction continues to be developed. However, one fact shows that human resources in Indonesia's construction field are still not ready to compete in terms of quality with the workforce of several countries in Asia. This research was conducted to determine the condition of Human Resource Management in the construction company in Indonesia. Data retrieval instruments use questionnaires and structured interviews at 50 randomly selected construction companies from different Indonesian regions. The data obtained is processed using quantitative data analysis using parametric statistics analysis. The results showed that Human Resource Management in Indonesia's construction company is in good or excellent condition provide 92%. This indicates that most of this industry has enforced and implemented policies related to this management. However, human resource planning patterns in Indonesia's construction company focus more heavily on Operational Planning, which means that this planning on construction companies in Indonesia is still project-oriented or short-term.
Keywords: Human Resource, Patterns, Operational, Construction.